Processes governing arsenic retardation on Pleistocene sediments: Adsorption experiments and model‐based analysis. Issue 5 (31st May 2017) - Rathi, Bhasker; Neidhardt, Harald; Berg, Michael; Siade, Adam; Prommer, Henning
Abstract: In many countries of south/south‐east Asia, reliance on Pleistocene aquifers for the supply of low‐arsenic groundwater has created the risk of inducing migration of high‐arsenic groundwater from adjacent Holocene aquifers. Adsorption of arsenic onto mineral surfaces of Pleistocene sediments is an effective attenuation mechanism. However, little is known about the sorption under anoxic conditions, in particular the behavior of arsenite. We report the results of anoxic batch experiments investigating arsenite (1–25 µmol/L) adsorption onto Pleistocene sediments under a range of field‐relevant conditions. The sorption of arsenite was nonlinear and decreased with increasing phosphate concentrations (3–60 µmol/L) while pH (range 6–8) had no effect on total arsenic sorption. To simulate the sorption experiments, we developed surface complexation models of varying complexity. The simulated concentrations of arsenite, arsenate, and phosphate were in good agreement for the isotherm and phosphate experiments while secondary geochemical processes affected the pH experiments. For the latter, the model‐based analysis suggests that the formation of solution complexes between organic buffers and Mn(II) ions promoted the oxidation of arsenite involving naturally occurring Mn‐oxides. Upscaling the batch experiment model to a reactive transport model for Pleistocene aquifers demonstrates strong arsenic retardation and could have useful implications in the management of arsenic‐free Pleistocene aquifers. Key Points: Arsenite, As(III), sorption onto natural Pleistocene sediments is controlled by primary (adsorption) and secondary (oxidation) processes Geochemical modeling framework improves interpretation of the analytical data and shows importance of coupling between the two processes 1‐D reactive transport simulations show significant impact of available sorption sites, As(III) and PO4 concentrations on arsenic retardation